15. Geriatric syndromes and nutrition status of elderly osteoarthritis patients - Luc, Tran Viet; Tam, Nguyen Ngoc; Thu, Nguyen Thi Hoai; Huyen, Vu Thi Thanh (Tạp chí Nghiên cứu Y học, 2023)
This study describes numerous characteristics of comorbidities and geriatric syndromes in elderly osteoarthritis patients at the National Geriatrics Hospital. A cross-sectional study on 184 knee osteoarthritis (OA) patients aged ≥ 60 years old treated at the National Geriatrics Hospital. The mean age of the patients was 73.12 ± 8.62 years, male patients accounted for 83.7%. Most participants (85.9%) had experienced 2 sides of knee OA, more than half of these participants (63.6%) were experiencing moderate pain. There were 73 patients with reduced mobility accounting for 39.7%. The dependency ratio of functional activities on the ADL scale was 32.6%, and on the IADL scale it was 35.9%. The number of participants using less than 5 drugs was 45.7%. More than half of the survey participants used polypharmacy accounting for 54.3%. There was a significant association between nutritional status and reduced physical function (ADLs and IADLs), impaired cognitive function, depression status and sleep disorder. Geriatric syndromes and risk of malnutrition are common in older OA patients, and assessment for them should be done routinely in these patients to early detect impaired physical activities, impaired cognitions, depression problems, sleep disturbances and progressive symptoms of knee osteoarthritis.